Effects Of Operational Factors On Biodegradation Of Phenol And P-Nitrophenol By Suspended And Immobilized Activated Sludge - Sam, Suat Peng (2020)
The presence of phenolic compounds in industrial effluents give rise to serious environmental problems owing to their high toxicity and bioaccumulation rate. This study aims to investigate the efficacy and kinetics of aerobic biodegradations of phenol and p-nitrophenol (PNP), respectively, by suspended and immobilized activated sludge at different operational conditions